2011
DOI: 10.1183/09031936.00151010
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide and the risk of wheezing in infancy: the Generation R Study

Abstract: We assessed whether exhaled nitric oxide fraction (FeNO), a marker of eosinophilic airway inflammation, at 6 months was associated with the risk of wheezing during the first 2 yrs of life.In the Generation R birth cohort, pre-and post-natal risk factors for respiratory morbidity and respiratory symptoms were assessed by questionnaires at 6 and 24 months. In 428 infants, off-line mixed oral/nasal FeNO was successfully measured during tidal breathing at 6 months. Complete data on FeNO and respiratory symptoms wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…On a cellular level, maternal tobacco smoke modified NOS activity in the fetal vascular bed in newborns [12]. Consistent with this observation, postnatal FeNO is modified by prenatal tobacco smoke exposure in offspring [16,17], interestingly enough, in an interaction with maternal atopy [16]. In contrast to the pre-and early postnatal situation, infancy and preschool age seems to be critical for further gene-environment interactions through exposures other than smoking and maternal atopy and their impact upon NO metabolism [4,5].…”
supporting
confidence: 67%
“…On a cellular level, maternal tobacco smoke modified NOS activity in the fetal vascular bed in newborns [12]. Consistent with this observation, postnatal FeNO is modified by prenatal tobacco smoke exposure in offspring [16,17], interestingly enough, in an interaction with maternal atopy [16]. In contrast to the pre-and early postnatal situation, infancy and preschool age seems to be critical for further gene-environment interactions through exposures other than smoking and maternal atopy and their impact upon NO metabolism [4,5].…”
supporting
confidence: 67%
“…The results were in line with earlier studies suggesting an association between FeNO early in life and respiratory symptoms, lung function, airways reactivity and/or asthma later in life [7][8][9][10][11]. The different populations studied, the different techniques used to measure FeNO and the different outcomes assessed may explain conflicting results with other studies [12][13][14]. CHAWES et al [12] showed that elevated FeNO at 1 month of age did precede transient early wheeze, but not persistent wheeze, and was unrelated to atopy.…”
contrasting
confidence: 42%
“…While there have been some relationships to wheezing early in life, 79,80 levels may be more related to IgE sensitization than asthma. 81 In addition, the on-line and off-line measurements used in infants may not adequately approximate the standardized technique used in older cooperative subjects, 82,83 …”
Section: Workgroup 4: Pulmonary Development (Group Membership: Table 1)mentioning
confidence: 99%